Evaluation on the use of plate positioning guide (PPG) on the placement accuracy of post-hemimandibulectomy plate reconstruction - Bulfendri Doni; Poerwati Soetji Rahajoe; Maria Goreti Widiastuti (Faculty of Dentistry, Universitas Gadjah Mada, 2022)
Improper placement of the reconstruction plate can lead to postoperative complications. Placing reconstruction plates that have arch for operation is made easier with the plate positioning guide (PPG) as a transfer method of reconstruction plate. This study aimed to assess the impact of PPG on the placement accuracy of reconstruction plate as determined by the symmetrical breadth of the mandibular arch and the consistent placement of reconstruction plate following hemimandibulectomy. According to the inclusion criteria, this was a retrospective cross-sectional study with 12 participants (n = 12) after hemimandibulectomy. Subjects were divided into PPG (n = 6) and Non-PPG (n = 6) groups. Measurement of the difference in the width of the mandibular arch and the height of the placement of the reconstruction plate between the reconstructed and non-resected sides in three positions (anterior, posterior, and angulus) was conducted using submentovertex radiographs and orthopantomogram (OPG) through the RadiAnt DICOM Viewer software. The placement accuracy of the reconstruction plates was analyzed using a one-sample t-test with p-value 0.05. The results showed that the placement accuracy of the reconstruction plate in the PPG group were accurate (p = 0.590), and the Non-PPG group was inaccurate (p = 0.000); with the independent sample test. There was a significant difference between the two groups (p = 0.000). Plate positioning guide provides better symmetry of the mandibular arch width post-hemimandibulectomy.